Lazarus Phenomenon in Medicolegal Perspective: A Case Report - Güven, Aykut Taner; Petridis, Gavril; Özkal, Şeyda Şebnem; Kalfoglu, Ersi Abacı (The Bulletin of Legal Medicine, 2017)
Auto-resuscitation or with the common name Lazarus phenomenon is unassisted return of spontaneous circulation after cardiac arrest. Lazarus phenomenon takes a little place in the medical literature. Doctors are reluctant to publish case reports because of apprehension of being sued due to medical malpractice. In the other hand Lazarus phenomenon is a rare and interesting topic for public media. In the forensic point of view, it’s important that if a Lazarus phenomenon is connected with medical negligence or not. All “Lasarus” case reports in the literature are informing that a time interval between declaration of death and noticing spontaneous circulation-inhalation from a few second to 33 minutes. Possibly there are no other example of 3 hours time interval between death declaration and noticing auto-resuscitation rather than in our case report.